A 4-year field measurement of N2O emissions from a maize-wheat rotation system as influenced by partial organic substitution for synthetic fertilizer. (1st June 2020) - Song, He; Wang, Jun; Zhang, Kui; Zhang, Manyu; Hui, Rui; Sui, Tianyi; Yang, Lin; Du, Wenbin; Dong, Zhaorong
Abstract: Soil N2 O emissions depend on the status of stoichiometric balance between organic C and inorganic N. As a beneficial management practice to sustain soil fertility and crop productivity, partial substitution of organic fertilizers (OFs) for synthetic fertilizers (SFs) can directly affect this balance status and regulate N2 O emissions. However, no multi-year field studies of N2 O emissions under different ratios of OFS to SFs have been performed. We conducted a 4-year experiment to measure N2 O emissions in a maize-wheat rotation in central China. Six treatments were included: total SF (TS), total OF, no N fertilizer, and ratios of to SF with 1: 2 (LO), 1: 1 (MO), and 2: 1 (HO), based on N content. Two incubation experiments were performed to further interpret the field data. In the first year, cumulative N2 O emissions (kg N ha −1 ) in LO, MO, and HO were 4.59, 4.68, and 3.59, respectively, significantly lower than in TS (6.67). However, from the second year onwards, organic substitution did not reduce N2 O emissions and even significantly enhanced them in the fourth year relative to TS. Soil respiration under OF-amended soils increased over the course of the experiment. From the second year onwards, there was no marked difference in mineral N concentrations between OF- and SF-amended soils. OF caused a drop in soil pH. Cumulative N2 O was negatively correlated with pH. Long-term organic substitution enhanced N2 O emissions produced via denitrification rather than nitrification and resulted in higher temperature sensitivity of N2 O emissions than TS. The enhanced N2 O emissions from the OF-treated soils were mainly attributable to accelerated OF decomposition, increased denitrification-N2 O emissions, and lessened N2 O reduction due to lower pH and greater NO3 − . These results indicate that OF substitution can reduce N2 O emissions in the first year, but in the long-term it can increase emissions, especially as soils warm. Highlights: Long-term organic substitution increased temperature sensitivity of N2 O emissions. Organic substitution could not reduce N2 O emissions in the long-term. Soil temperature mediated N2 O peak sizes in the wheat season. Organic substitution enhanced N2 O emissions produced via denitrification.